(untitled) (Archives of Mechanics - Test, 2002)
Constitutive modeling based on the so-called rational phenomenology (materials science approach) has been applied to take into account strain hardening, strain-rate sensitivity, thermal effects and evolution of microstructure in a polycrystalline tantalum. A wide range of strain rate in shear (10-4 1/s < Γ Ì‡ < 5·103 1/s) and homologous temperature (0.05 < Θ < 0.2) is considered. Behavior of tantalum is understood as an example for BCC polycrystalline metals. The constitutive modeling provided a possibility to determine all material constants via the experimental results obtained on thin tubular specimens using a fast hydraulic machine and a torsion Hopkinson bar. Finally, the model predictions are demonstrated by numerical simulations for different history paths in strain rate and temperature.